CRITICAL THINKING SKILLS OF YEAR 10 SANGUINIS STUDENTS IN LEARNING BASED ON NITENI, NIROKKE, AND NAMBAHI - Astuti, Fuji; Widodo, Sri Adi; Taufiq, Irham; Pusporini, Widowati; Mansor, Kamarul Ariffin (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
The study aimed to examine whether Tri-N-based trigonometry instruction improved students' critical thinking skills and sanguine personality. Single-subject research with an ABA design was the method used in this study. The stages of this study were the initial Baseline (A), the Intervention (B), and the second Baseline (A'). Year 10 science students with sanguine personalities who were chosen using a purposive sampling technique served as the study's subjects. This study employed observation methods, testing tests, and documentation for data collection. Data analysis within and between conditions are the methods used to analyze data. The findings of this study revealed that using Niteni, Nirokke, and Nambahi learning on trigonometry improved students' critical thinking skills with sanguine dispositions.